Video Animasi 2D Pengenalan Bangun Datar Pada Pembelajaran Matematika - Welly Desriyati (STEKOM PRESS, 2021)
Rapid technological advances make print communication media begin to be shifted by information media that utilizes computer technology as a means of delivery. Technological developments change the teacher's task from being a teacher to a facilitator who provides convenience in learning. SD Negeri 004 Bangsal Aceh is one of the schools that still applies the mathematics learning process using textbooks so that students do not understand the lesson. Teachers are required to make changes in teaching patterns in the classroom, one of which is with animated videos. This study uses the Multimedia Development Life Cycle (MDLC) method covering concept, design, collecting material, assembly, testing and distribution. The final result of this research is an animated video of mathematics learning about the material of flat shapes. Animated videos are used as an interesting and effective means of information and learning media. Besides that, it can also improve students' understanding and skills in learning mathematics, especially the material of flat shapes